Development and application of an LC–MS/MS method for quantification of fosmidomycin in human and rat plasma - Christoph Pfaffendorf; Keanu D. Sackmann; Johannes Mischlinger; Jean Claude Dejon-Agobé; Oumou Maïga-Ascofaré; Ebenezer Ahenkan; Ayôla Akim Adegnika; Michael Ramharter; Philipp Uhl; Gert Fricker; Sebastian G. Wicha (Malaria Journal)
Abstract Background Malaria still poses a significant burden on global health, with millions of cases reported annually and rising resistance to current treatments, emphasizing the need for new therapeutic strategies. Fosmidomycin, initially recognized for its antibacterial properties, has emerged as a promising candidate in the fight against malaria. Methods In this study, a sensitive and robust LC–MS/MS method for quantifying fosmidomycin in human and rat plasma was developed and validated. Plasma samples were prepared using a simple protein precipitation method with 10% trichloroacetic acid (TCA). The assay featured a rapid run time of 5 min, and validation was performed according to the European Medicines Agency's guidelines. Results The method validation confirmed its selectivity, linearity, accuracy, precision, and stability. Notably, the calibration range was established from 0.25 to 15 mg/L, demonstrating improvements over previous methodologies with lower limits of quantification of 0.5–1.0 mg/L. Using the developed LC–MS/MS method, plasma samples were analysed from a clinical trial conducted in Gabon, as well as from a pharmacokinetic study involving male Wistar rats, revealing viable pharmacokinetic profiles for fosmidomycin. Conclusions These findings confirm the utility of the developed analytical method for supporting the clinical development of fosmidomycin as a potential therapy for malaria.